Factorial design to obtain magnetized poly(ethyl acrylate-co-divinylbenzene) - Kelly Lúcia Nazareth Pinho de Aguiar; Kaio Alves Brayner Pereira; Marcelo Sierpe Pedrosa; Márcia Angélica Fernandes e Silva Neves (Polímeros)
Abstract Magnetized polymers are produced by incorporating magnetic particles in a polymeric matrix. This article describes the use of the suspension polymerization technique using ethyl acrylate and divinylbenzene as monomers, in the presence of heptane and/or toluene as diluent, initiated by free radicals. To produce the polymer, we first performed fractional factorial planning to help visualize the factors that could influence the results, to verify the action of different responses simultaneously. Five factors were evaluated that influence the production of the polymer and incorporation of iron in the matrix. Infrared spectroscopy, X-ray fluorescence, magnetic force testing and scanning electron microscopy were used to characterize the samples. The results indicated the positive influence of the quantity of the polymerization initiator on the yield of the process and the negative effect of the content of divinylbenzene on the incorporation of iron in the matrix and on the magnetic force.